Spatial Aspects in the Multilevel Models Construction - Łaszkiewicz, Edyta (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
Multilevel (hierarchical) models are used for analysing data for which getting a few levels of the aggregation is possible. In the simplest case it is possible to present the way of organizing the levels in the form of the hierarchical structure or applying the cross-classification of data. The multilevel model construction might be used in the spatial analyses. The purpose of this article is to present the possibility of spatial processes analyses using multilevel models. The implementation techniques of the already existing multilevel models to the spatial structure were discussed. Additionally, the possibility of the traditional multilevel models rebuilding, towards taking into account spatial interactions, was present.